LATAR HISTORIS DAN PRINSIP AJARAN ALIRAN ASY’ARIYAH BESERTA RELASINYA DENGAN ALIRAN MU’TAZILAH - Muhammad Soadikin; Indo Santalia (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
This article comprehensively discusses the historical development and main teachings of the Asy'ariyah theological school as one of the main currents in the Sunni Islamic intellectual tradition. Using a descriptive qualitative approach with library research and historical analysis methods, this study traces the emergence of Asy'ariyah as a response to the dominance of Mu'tazilah rationalism in the 9th to 10th centuries AD. The findings show that Abu al-Hasan al-Asy'ari developed a moderate theological framework that harmonized reason and revelation through the concepts of tafwīd and ta'wīl, while rejecting both rational and textual extremism. The discussion also outlines the main teachings of Asy'ariyah, including its understanding of the nature of God, the concept of kasb in human actions, the eternity of kalamullah, the possibility of ru'yah, and its moderate position on major sinners. In addition to emphasizing the fundamental differences between Asy'ariyah and Mu'tazilah, this article identifies the dialectical relationship and intellectual influence between the two schools of thought. The conclusion shows that Asy'ariyah contributed significantly to shaping a moderate Islamic theological framework and had a broad influence on the development of Islamic thought until the modern era.